It's Our Story: Parents and Carers' Experiences during the Pandemic. (September 2022) - Pybus, Katie; McEwan, Jean; Garthwaite, Kayleigh; Power, Maddy; Patrick, Ruth; Corley, Sydnie
Parents and carers taking part in the Covid Realities research programme came together to create a zine about their experiences during the pandemic, as well as focusing on what needs to change in the future and why. The zine was developed and designed collaboratively by participants and artist Jean McEwan, and supported by the research team, at a series of three virtual zine-making workshops during February and March 2021. The aim of the zine is to directly represent the voices of parents and carers, therefore giving power and expression to those with firsthand experience of living on a low income, who are frequently marginalised in broader policy-making conversations. Making zine pages together in small groups with the chance for conversation and discussion during the workshops also provided a source of social support for contributors. This is especially pertinent in the pandemic context, where it has been harder for people to find social spaces to connect.